PENINGKATAN PENGETAHUAN BUDAYA MELAYU MELALUI PEMBELAJARAN BERBASIS KONTEKSTUAL (CTL) KELAS IV SDN 191 PEKANBARU - Putra, Elpri Darta; Ramadan, Zaka Hadikusuma; Mulyani, Eva Astuti (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2020)
This research aims to describe to enhancement malay cultural knowledge of students Elementary School in Pekanbaru. The research was conducted at SDN 191 Pekanbaru City with the focus of the object of the research werw the students of class VI. The design of this research was PTK (Classroom Action Research). The initial data of students was obtained namely 66.38 and in the first cycle 72.75 increased by a difference of 6.37 units. While the average student learning outcomes in the first cycle of 72.75 and in the second cycle of 78.81 has increased by a difference of 6.06 units. The action is carried out by the teacher, by the teacher together with the students, or students under the guidance and direction of the teacher, with a view to improving and improving the quality of learning.